(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2018)
Methods: An observational cross sectional study, which includes 116 patients of sputum smear positive pulmonary TB of age 18 or above. Further, detailed history taking regarding different demographic profile was done. Also, they were subjected to CB-NAAT and rifampicin resistant cases were considered as MDR-TB. Results: Proportion of MDR-TB was 31.89% among retreatment TB cases. 56.75 % (n=21) of MDR-TB cases were between the age group of 21-40 years. Proportion of MDR-TB was higher among males (75.67%), married (59.45%) and rural dwellers 59.45%. Proportion was 61.76% among patients with BMI <16; 31.57% with BMI 16-16.99, 28.57% with BMI 17-18.49 and 5.7% with BMI 18.50-24.99. MDRTB proportion was less 29.72% (n=11) in patients with history of TB contact in family. Pulmonary TB including MDR-TB was more common among illiterates (37.83% among MDR). Conclusion: Proportion of MDR-TB was high among retreatment cases in north India. Among them low BMI and education status are modifiable factor and this study signifies that MDR-TB burden can be reduced by improving health and education status of patient.